Everything for the Nation: The Re-founding and Return of the State in the Bolivarian Revolutions - Felipe Burbano de Lara (Íconos, 2015)
This article examines the so-called return of the state in the three Bolivarian Revolutions (Venezuela, Bolivia and Ecuador) analyzing the discourses of Hugo Chavez, Evo Morales and Rafael Correa. The idea of a return of the state suggests clearly that if the state was seen as the problem in the 1980s and 1990s, in the processes of the new left in Latin America it has been presented as the solution. However, beyond certain general issues, there have been few analyses that explain how the state has returned in the Bolivarian Revolutions y how this return has redefined the political context and analyze the implications of this return. This article demonstrates how the state has returned in the three cases in relation to two other powerful phenomena: the promise of re-founding the nation and patriotism. It is concluded that the convergence of these three elements –re-foundationalism, the nation and the state– configured a powerful collective identity containing moral and emotional elements which link the leaderships of the three with a reconstituted political community.